(untitled) (Research, Society and Development, 2022)
The discussions mediated by critical and post-critical curriculum theories highlight that the curriculum and school should not be conducted in isolation. The objective of this article is to discuss the practical implications that were experienced from the teachers’ point of view for the dialogue between the school and the curriculum in Basic Education. Using the observation method, the qualitative research was carried out by two teachers in two schools of the State Education system, in the State of Espírito Santo. The reflections made throughout this research direct in a theoretical way a necessary look to the relationships that are experienced in everyday life at school, thus fostering the discussion of what kind of curriculum we want by questioning which schools we intend to have. In conclusion, although it is a space of conflicts, the curriculum and school together should go through spaces that allow them to lead to practical attitudes in the school environment.